THEORETICAL PRINCIPLES OF ANTI-BLOCKING AND ANTI-SLIPPAGE SYSTEMS OF NEW GENERATION - N. N. Hurski; Y. I. Slabko; R. I. Fourounjiev; A. L. Homich (Наука и техника)
A new approach on creation of anti-blocking and anti-slippage systems of mobile machines based on observation of actual forces/moment values in «road-wheel-car» contact and their derivatives is considered in the given paper. The paper describes theoretical principles and an operational algorithm of anti-blocking and anti-slippage systems.